KEMAMPUAN BERPIKIR KRITIS DITINJAU DARI ADVERSITY QUOTIENT PADA CHALLENGE-BASED ON DIFFERENTIATED LEARNING BERBANTUAN WEBSITE STEM - Setiawan, Ananda Verry; Ardiansyah, Adi Satrio; Suparsono, Suparsono (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2026)
21st century education emphasizes the importance of critical thinking skills. Data from Programme for International Student Assessment indicate that these skills still need improvement, thus requiring instructional innovations such as Challenge-Based on Differentiated Learning (CB-DL) supported by a STEM-based website. This study aims to (1) analyze the quality of instructional innovation in enhancing critical thinking skills, (2) examine the effect of Adversity Quotient (AQ) on critical thinking skills, and (3) describe critical thinking skills in terms of AQ. The study employed mixed methods approach. Quantitative data were collected through questionnaires and tests and analyzed using RStudio, while qualitative data were collected through interviews and analyzed using technique triangulation. The results show that CB-DL supported by a STEM-based website is of high quality in improving critical thinking skills. In addition, AQ has a positive effect of 12.92% on critical thinking skills. The findings indicate that climbers-type participants fulfill the indicators of interpretation, analysis, evaluation, inference, explanation, and self-regulation, whereas campers-type participants fulfill interpretation, analysis, evaluation, inference, and explanation. This study provides significant empirical contributions to improving critical thinking skills.